Improving energy efficiency through technology trends, investment behaviour and policy design - Florax, R. J. G. M. 1956-; Groot, Henri L. F. de; Mulder, Peter 1974- (Edward Elgar Publishing, 2011)
This innovative book explores the adoption of energy-saving technologies and their impact on energy efficiency improvements. It contains a mix of theoretical and empirical contributions, and combines and compares economic and physical indicators to monitor and analyse trends in energy efficiency. The authors pay considerable attention to empirical research on the determinants of energy-saving investment including uncertainty, energy-price volatility and subsidies. They also discuss the role of energy modelling in policy design and the potential effect of energy policies on technology diffusion -- Source other than Library of Congress.